Intraductal papillomas of the breast. The problems of the pathogenesis, treatment, and prevention of intraductal carcinoma - G. Kh. Khanafiyev; S. A. Berzin; U. Yu. Maltseva; A. E. Mazur (Опухоли женской репродуктивной системы, 2014)
The paper summarizes the results of follow-ups of 624 patients operated on for clinically , radiologically, and cytologically verified intraductal papillomas (IDP) of the breast. Morphological study of the intraoperatively removed material revealed papillomas in 91.4 % of the patients, epithelial proliferation foci without dysplasia in 3.9 %, fibrosis and hyalinosis in 2.3 %, and lymphoid proliferations in the duct walls in 0.6 %. Immunohistochemical study of periductal tissues identified cell receptors to estrogens and progesterone in 44% of cases. Antiestrogen treatment versus no treatment postoperatively contributed to a reduction in the rate of recurrent IDP(from7.9to2.7 %)and to the prevention of intraductal carcinoma (3.2-0 %). This suggests that estrogens play an important role in the pathogenesis of both processes when theperiductal tissue cells contain sex hormone receptors. If they lack the receptors, resorption of pathological secretion gives rise to autoimmune inflammation, hyalinosis, fibrosis of the walls of ducts, their luminal obstruction and as a consequence to duct ectasias and breast cysts.